From inefficient behind-the-border policies to inefficient trade agreements: A two-tier asymmetric information model - Bouët, Antoine; Laborde Debucquet, David; Martimort, David (Royal Economic Society, 2021)
We consider a general equilibrium model of international trade with two layers of informational asymmetries. Private information of Home producers on costs affects the design of ‘behind-the-border’ policies reflecting the political influence of inefficient producers. Home's supply is contracted, causing trade, and motivating the use of tariffs. Eliminating those instruments by means of a trade agreement may become impossible once Home has also private information on its redistributive concerns. Home, when subject to strong influence by inefficient producers, might be reluctant to adopt free trade, which may lead to limited tariff cuts and give a role for export subsidies.